Using the System of Least Prompts to Teach Personal Hygiene Skills to a High School Student with Comorbid Visual Impairment and Autism Spectrum Disorder. (November 2017) - Probst, Kristi M.; Walker, Virginia L.
Introduction: This study evaluated the effectiveness of a workshop and follow-up coaching sessions on the implementation of the system of least prompts procedure by classroom team members and explored whether this intervention resulted in personal hygiene skill acquisition by a male high school student with comorbid visual impairment and autism spectrum disorder. Methods: Implementation fidelity data were analyzed descriptively through visual analysis. A multiple baseline design across behaviors was utilized to evaluate the effectiveness of the system of least prompts procedure on student skill acquisition. Results: Implementation fidelity was high and increased over the course of the study: paraeducator 1: 93.9% (range, 70 to 100%); paraeducator 2: 78.2% (range, 11 to 90%); and special education teacher: 94.1% (range, 35 to 100%). In addition, the student's independent performance improved from baseline to intervention across each targeted skill, with Tau -U scores as follows: cleaning the augmentative and alternative communication device: 0.78; washing hands: 0.76; and brushing teeth: 0.92. Classroom team members found both the training procedures and the system of least prompts intervention to be of value and effective. Discussion: During intervention, classroom team members implemented the system of least prompts with fidelity and the student mastered each skill. These results are promising and add to the significantly limited literature on instructional interventions for students with comorbid visual impairment and autism spectrum disorder. Implications for practitioners: Classroom team members can effectively be taught to use the system of least prompts with students with comorbid visual impairment and autism spectrum disorder. Furthermore, the intervention might be used to increase independent functioning for students with these comorbid conditions.